MON-LB67 Bisphosphonate Related Ocular Inflammation - Seetharaman, Kavita (J Endocr Soc, 2020)
Introduction: Osteoporosis is a major public health problem, increasing in incidence with the growth of the aging population. It affects over 200 million women worldwide and is associated with fragility fractures leading to increased morbidity, mortality and poor quality of life (1). Bisphosphonates are among the most widely used first line forms of treatment for management of osteoporosis. They have a structure like pyrophosphate and inhibit bone resorption by attaching to hydroxyapatite binding sites on the bone in areas with active resorption. While initiating treatment with bisphosphonates, endocrinologists generally discuss side effects including gastrointestinal symptoms related to gastroesophageal reflux disease and gastritis, acute phase reactions related to infusion of the bisphosphonates, musculoskeletal pain, hypocalcemia, osteonecrosis of the jaw, and atypical femur fractures. There are rare but severe side effects causing ocular inflammation related to bisphosphonate use - Bisphosphonate Related Ocular Inflammation (BROI). While these are rare based on few case reports, they are significant side effects, which if patients are not aware of or not addressed in timely manner can result in vision loss. We report a clinical scenario of a patient who experienced bisphosphonate-related ocular inflammation. Clinical History: 62-year-old female with cerebral palsy presented to the emergency room with 1 day of marked left eye redness and swelling. When the symptoms began, she felt that her eye was itchy. She had mild left eye discomfort. She did not perceive any decreased visual acuity. Patient had her first infusion of bisphosphonate, 4 days prior to the emergency room visit. On Exam: She was alert, no apparent distress, left eyelids were swollen, almost completely shut with minimal discoloration, there was underlying severe chemosis and conjunctival redness, pupils equal and round, visual acuity 20/100 OD and 20/100 OS. She was diagnosed with allergic conjunctivitis, and advised to apply Tobradex drops and Diphenhydramine, and to follow-up in eye clinic. Scleritis related to bisphosphonates was also considered as a possible cause of her symptoms. The patient called the endocrinologist about the eye symptoms the following day. The endocrinologist also raised the possibility bisphosphonate related ocular inflammation and advised to be seen in ophthalmology clinic urgently. The endocrinologist also communicated with the ophthalmologist indicating that her eye symptoms could be due to inflammatory response related to bisphosphonates and to consider starting systemic steroids. The patient was seen in ophthalmology clinic the following day: The ophthalmology exam revealed severe orbital inflammation with conjunctival chemosis OS: Table 1.She was started on Prednisone 80mg a day with tapering by 10mg daily over the next 2 weeks. She was also advised to apply Durezol eye drops twice a day. She was referred to Oculoplastics for further evaluation. Table 1: Oculoplastics evaluation next day Table 2: Revealed orbital inflammation with good initial response to steroids and advised to continue prednisone taper. Table 2: On the 2 weeks follow up: Table 3: Resolved orbital inflammation and was advised to stop prednisone Table 3: Clinical Discussion: Bisphosphonates are widely prescribed and effective forms of treatment for osteoporosis in preventing fractures. Ocular side effects are rare but reported over the past 2 decades (2). First time users of bisphosphonates are at a higher risk compared with nonusers (3).There is also an association of bisphosphonate-related ocular inflammation (BROI) with coexisting inflammatory conditions that associated with ocular inflammation, such as rheumatoid arthritis, ankylosing spondylitis, psoriasis, inflammatory bowel disease, systemic lupus erythematosus or sarcoidosis (4,8).Symptoms related to BROI typically occur within 24 to 72 hours of the bisphosphonate exposure but can range between few hours to 3 years. Those who receive systemic bisphosphonates present earlier compared to orally administered bisphosphonates (5,6,7). In prior case reports, patients presented with flu like symptoms, lasting for lasting for 24 to 72h prior to onset of orbital disease (5). The range of ocular inflammation is variable, and can include conjunctivitis, uveitis, scleritis, episcleritis and keratitis. The symptoms can be unilateral or bilateral. Discontinuation of bisphosphonates is necessary for resolution of ocular inflammation (7).The postulated cellular mechanism causing BROI is as follows: Bisphosphonates are secreted into the lacrimal system, and induce an inflammatory response resulting in release of cytokines that results in ocular inflammation: Fig 1: (9). Fig 1: It is unclear as to why BROI is a rare side effect, though related to release of inflammatory reactants, which are also responsible for the more common flu like side effect. The risk of BROI is increased in those with associated inflammatory condition (arthritis or inflammatory bowel disease). It is possible that in individuals susceptible to inflammatory disorders, there is pre-existing infiltration of the lacrimal gland with mononuclear cells which causes a robust local inflammatory response to bisphosphonate treatment in the eye. Our patient with cerebral palsy and learning disability, was taken to the emergency room within few hours of onset symptoms and signs of ocular inflammation. Though she was diagnosed with severe orbital inflammation, she did not express eye pain, which is commonly seen in scleritis. Through multidisciplinary teamwork between the emergency physician, endocrinologist, ophthalmologist and oculoplastic specialists, she was promptly started on systemic steroids and her symptoms resolved completely with no vision loss. While considering bisphosphonates as an option for osteoporosis treatment, the endocrinologist should discuss the rare but serious complications of BROI. With use of bisphosphonates in the aging population to treat osteoporosis, specific attention should be given to underlying eye disease, inflammatory conditions, and cognition. References: 1. IOF statistics: (https://www.iofbonehealth.org/epidemiology). 2. Clark EM, Durup D. Inflammatory eye reactions with bisphosphonates and other osteoporosis medications: what are the risks?. Ther Adv Musculoskelet Dis. 2015;7(1):11–16. doi:10.1177/1759720X145664243. Etminan M, Forooghian F, Maberley D. Inflammatory ocular adverse events with the use of oral bisphosphonates: a retrospective cohort study. CMAJ. 2012;184(8):E431–E434. doi:10.1503/cmaj.1117524.French DD(1), Margo CE. Postmarketing surveillance rates of uveitis and scleritis with bisphosphonates among a national veteran cohort. Retina. 2008 Jun;28(6):889-93. doi: 10.1097/IAE.0b013e31816576ef. 5.Herrera I, Kam Y, Whittaker TJ, Champion M, Ajlan RS. Bisphosphonate-induced orbital inflammation in a patient on chronic immunosuppressive therapy. BMC Ophthalmol. 2019;19(1):51. Published 2019 Feb 14. doi:10.1186/s12886-019-1063-8 6. Ehsan Rahimy, Simon K. Law. Orbital inflammation after zoledronate infusion: an emerging complication.https://doi.org/10.1016/j.jcjo.2012.09.011 7. Frederick W. Fraunfelder, M.D Bisphosphonates and Ocular Inflammation. NEngJ Med 2003; 348:1187-1188. DOI: 10.1056/NEJM200303203481225 8.Pazianas M(1), Clark EM, Eiken PA, Brixen K, Abrahamsen B. Inflammatory eye reactions in patients treated with bisphosphonates and other osteoporosis medications: cohort analysis using a national prescription database. J Bone Miner Res. 2013 Mar;28(3):455-63. doi: 10.1002/jbmr.1783.9.Keith Thompson and Michael J. Rogers. New Insights into Old Drugs. BoneKEy-Osteovision. 2006 August;3(8):5-13